Identifying best-practice strategies for managing residential caregivers working with children at risk - Reznikovski-Kuras, Anna; Gerasimenko, Anna (International Journal of Child, Youth and Family Studies, 2020)
Residential caregivers are the central figures responsible for the children in their charge. Their work is physically and emotionally taxing, and carried out under pressure: they are prone to burnout. In addition, their status is lower than that of other staff. This study aimed to identify the strategies to improve caregiver functioning that have been adopted in Israel’s residential social-service facilities, and to examine the extent of their implementation. A two-stage, mixed-methods study design was employed. In the qualitative stage, six successful care facilities were identified; their directors were interviewed in depth using the Learning from Success method. In the quantitative stage, a survey was administered to 95 directors, using open and closed questions. Six best-practice strategies for working with caregivers were identified: careful screening, training, ongoing supervision, personal and professional support mechanisms, flexible schedules, and a clear work plan and procedures. While these strategies were applied to some extent in most facilities, they varied in scope and implementation. Using a regression model, we found a connection between the implementation of these strategies and the directors’ satisfaction with the caregivers’ work. We discuss recommendations that can help directors incorporate the six strategies in residential homes and meet the challenges directors face in their work with caregivers.